Complex interaction between allopurinol-induced uric acid reduction and glycemic control: a clinical and molecular study - Pongoh, Lucyana; Manoppo, Jonesius Eden; Supit, Gerry; Supit, Alva (Faculty of Medicine, Universitas Diponegoro, 2024)
Background: Diabetes mellitus type 2 (DMT2) and hyperuricemia are two prevalent metabolic diseases worldwide, including in Indonesia. In fact, in the Minahasa tribe, the prevalence of these diseases is among the highest in Indonesia. The interaction between hyperuricemia and DMT2 level is inconclusive, as previous studies about whether allopurinol and its related uric acid reduction correlate with insulin resistance have shown conflicting results.Objective: To examine whether allopurinol-induced uric acid reduction can modify insulin resistance in nondiabetic Minahasan male subjects and study the putative molecular mechanisms of this interaction.Methods: The clinical part of this research was a pseudo-experiment with a pre-test/post-test design. Twenty nondiabetic Minahasan male subjects were subjected to the daily dose of 300 mg allopurinol for three months. Plasma glucose, uric acid, and insulin levels were measured pre- and post-treatment. Homeostatic model assessment of insulin resistance (HOMA-ir) values were calculated by the Oxford HOMA calculator. For the wet lab experiment, the human embryonic kidney cell line was treated with tolerable allopurinol. The expression of glucose transporter 4 (Glut4) mRNA, an insulin-inducible glucose transporter was analyzed by quantitative real-time polymerase chain reaction (qPCR).Results: In nondiabetic Minahasan male subjects, allopurinol administration decreased uric acid serum level, but did not affect plasma glucose and insulin levels. In fact, there is a trend of increasing HOMA-ir among the subjects following allopurinol administration. In vitro, allopurinol treatment also did not increase Glut4 expression, suggesting that allopurinol's effect on diabetes control has other, complex mediative pathways.Conclusion: Allopurinol administration and its related uric acid plasma reduction does not significantly affect insulin resistance; a trend however exists that allopurinol and uric acid reduction increased HOMA-ir. At the molecular level, Glut4 expression is not affected by allopurinol.